QUARTER LIFE CRISIS MENGENAI KESIAPAN MENIKAH PADA MASA DEWASA AWAL - Aundrea, Felizhia Ceccile; Riyanto, Rosid Ibnu (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
This paper explores the phenomenon of quarter-life crisis in the context of marriage during early adulthood. In this transitional phase, individuals face challenges related to identity, career, and interpersonal relationships. Social pressure and stigma can influence the decision to marry, leading to anxiety and confusion. Emotional and socio-emotional readiness are crucial before getting married, making it essential to prepare adequately for building a healthy relationship. Through a review of literature from the past ten years, this paper reveals the complexities of marriage at a young age and emphasizes the importance of communication and social support in navigating this crisis.